EFEITOS DOS INIBIDORES DO HIDROLISADO DA CASCA DE COCO VERDE NA PRODUÇÃO DE ETANOL DE SEGUNDA GERAÇÃO POR Saccharomyces cerevisiae GENETICAMENTE MODIFICADA - Lage, Matheus Silva (2020)
Ethanol production from lignocellulosic waste is one of the main renewable sources to supply the growing energy demand and contribute to the production of conventional fuels. Green coconut shell is a waste discarded by the ton, becoming an environmental p